Intraoperative radiotherapy during breast-conserving surgery using a miniature x-ray generator (Intrabeam®): theoretical and experimental background and clinical experience. (January 2012) - Wenz, Frederik; Blank, Elena; Welzel, Grit; Hofmann, Frank; Astor, Daniela; Neumaier, Christian; Herskind, Carsten; Gerhardt, Axel; Suetterlin, Marc; Kraus-Tiefenbacher, Uta
Breast cancer is currently the most frequent indication for intraoperative radiotherapy with increasing numbers worldwide. Intraoperative radiotherapy can be used as a tumor bed boost followed by whole breast radiotherapy, or as a distinct form of accelerated partial breast irradiation in selected patients. This article summarizes the theoretical background including pattern of recurrence and distribution of tumor cell foci in the breast and discusses the rationale for intraoperative radiotherapy, especially using a miniature x-ray generator (Intrabeam ® ). The concepts of how to avoid geographic and temporal miss by giving radiotherapy during surgery to the open wound cavity are described. Experimental and clinical experience is presented based on in vitro experiments and more than 300 treated patients in a single department with mature follow-up.